Empowerment of mosque community with ultraviolet light sterilisator robot - Iswanto Suwarno; Nia Maharani Raharja; Alfian Ma’arif; Arya Adiningrat; Adhianty Nurjanah; Dhiya Uddin Rijalusalam; Carlos Sánchez-López (Peneliti Teknologi Teknik Indonesia, 2021)
The first case of the COVID-19 disease was reported in Wuhan. Indonesia is also one of the countries affected by the COVID-19 pandemic. This case was first detected in two patients in Jakarta. The spread of the COVID-19 virus is so fast and spreads to all regions in Indonesia. Due to the rapid spread of the virus, efforts are needed to prevent it from spreading. Several local governments in Indonesia have implemented a lock down system to cut the spread of the COVID virus. Entering a new era, the government urges the public to adopt a new way of life to prevent wider transmission while preventing infection, namely wearing masks, maintaining distance, maintaining cleanliness, especially hands. The government's call to enter a new era was also followed by the mosque. However, this appeal is very difficult to implement for the new era because the mosque does not yet have a sterilizer to kill bacteria and germs. The sterilizer is used to sterilize the floor of the mosque. The service team tries to offer solutions to these problems with a touch of science and technology through community empowerment programs. The solution is offered with an ultraviolet lamp mounted on a sterilizing robot that can be remotely controlled. Ultraviolet lamp sterilizer robot is able to sterilize the floor of the mosque and the walls of the mosque.